Availability of Iron, Manganese, Zinc and Copper in some Soils of Western Rajasthan - Dhir, R P; Sharma, B K; Joshi, D C (Annals of Arid Zone, 2016)
A wide spectrum of soils spread over 35,000 sq km area of Nagaur and Jodhpur districts was subjected to analysis for available forms of various micronutrient elements. Amongst the various soils found in the area, Parbatsar series showed appreciably high value of all the nutrient elements. Kumprawas and Silgaon soils were found to have above average value of zinc whereas Palaripichkian variant, Silgaon and Khajwan soils had more of copper in comparison to other soils. Available manganese ranged mostly from 10 to 20 ppm but it was less than 7 ppm in Dune soils. An assessment of the nutrient status of the soils in light of the currently available criteria suggests that all the soils have adequate level of micronutrient elements, only the Dune soils appear marginal in respect of manganese and zinc. Available manganese and copper contents were positively and significantly correlated with clay, silt and organic carbon content of the soils. Iron and zinc were not significantly influenced by any of the soil parameters studied